Catalyst for preparing 2, 6-diisopropylnaphthalene through naphthalene alkylation reaction as well as preparation method and application of catalyst
By performing the hydrogen-type mordenite heat treatment and zirconium sulfate loading, a catalyst with sulfated zirconia structure is formed, and the problems of low yield and ease of inactivation in the prior art are solved, and a high-efficiency and good selectivity of decalination reaction is achieved.
Patent Information
- Application Number
- CN202411903515.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
AI Technical Summary
The catalysts for preparing 2,6-diisopropylnaphthalene in the prior art have problems such as low yield, easy deactivation of the catalyst and many side reactions.
By heat-treating the acid dispersion of hydrogen mordenite, some aluminum atoms are removed, and zirconium sulfate is loaded on the basis of it to form a sulfated zirconium oxide structure, enhancing the acidity and selectivity of the catalyst.
It improves the yield and selectivity of the catalyst, reduces side reactions, extends the active life of the catalyst, and inhibits carbon accumulation.
Smart Images

Figure BDA0005203823960000041 
Figure BDA0005203823960000051 
Figure BDA0005203823960000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fine chemical industry, relates to the technical field of reaction for preparing high value-added chemicals by alkylation reaction of polycyclic aromatic hydrocarbons, and specifically relates to a catalyst for preparing 2,6-diisopropylnaphthalene by alkylation reaction of decacyclic aromatic hydrocarbons, and a preparation method and application thereof. Background Art
[0002] Polyethylene naphthalate (PEN) has significant advantages in physical and mechanical properties, gas barrier properties, chemical stability, heat resistance and UV resistance. As a key raw material, PEN is widely used in cutting-edge industries such as aerospace, national defense, 5G communications, smart cars, sensors and smart medical care, and is one of the most promising emerging polymer materials in the 21st century.
[0003] 2,6-Diisopropylnaphthalene (2,6-DIPN) is a key raw material for the synthesis of high-performance PEN resins. Its synthesis process is complex, production efficiency is low, and product separation is difficult, resulting in high production costs for 2,6-DIPN. However, traditional methods mostly use liquid acid catalysts such as hydrofluoric acid, sulfuric acid, or anhydrous aluminum chloride. These traditional liquid catalysts are highly corrosive, complex to operate, and require high equipment. They also produce a large amount of harmful waste liquid and cause serious environmental pollution. In addition, the reaction usually requires high temperature and high pressure, which leads to insufficient catalyst activity, selectivity, and stability.
[0004] In the prior art, the synthesis of 2,6-DIPN is mainly achieved by alkylation reaction of naphthalene and propylene on zeolite catalysts. Zeolite catalysts stand out from many alkylation catalysts due to their unique shape selectivity, high specific surface area, easy separation from liquid products and green environmental protection characteristics, and become the preferred catalyst for the preparation of 2,6-DIPN. Among them, mordenite (MOR), which has a suitable pore size, eight-membered ring and twelve-membered ring structure, has been proven to have good catalytic performance in naphthalene isopropylation reaction. However, the existing molecular sieve catalysts still have the following problems: the distribution and strength of acid sites are difficult to accurately control, resulting in increased side reactions. In addition, the microporous structure of zeolite limits the diffusion performance of reactants and products, thereby reducing the reaction efficiency, which in turn leads to serious catalyst carbon deposition problems. However, the removal of framework atoms only by acid or alkali treatment often leads to the loss of acid sites, which reduces the catalytic efficiency. Summary of the invention
[0005] In order to solve the problems of low yield, easy catalyst deactivation and many side reactions in the catalyst reaction for preparing 2,6-DIPN in the prior art, the present invention aims to provide a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction, a preparation method and application thereof. The catalyst improves the reaction activity of zeolite acid sites and realizes the regulation of zeolite pore structure, and has the advantages of high yield and not easy to deactivate in catalyzing decalinization reaction to prepare 2,6-DIPN.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction, comprising the following steps:
[0008] The acid dispersion of hydrogen-type mordenite is heat-treated, filtered, and calcined once to obtain acid-treated mordenite;
[0009] The zirconium sulfate dispersion of acid-treated mordenite is treated at 60-90° C. for 2-8 hours, filtered, and calcined twice to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0010] Furthermore, the heat treatment temperature is 60-90° C. and the time is 2-8 hours.
[0011] Furthermore, the acid solution is an aqueous solution of one or two of nitric acid, sulfuric acid, hydrochloric acid and citric acid.
[0012] Furthermore, the acid dispersion of hydrogen-type mordenite is prepared by dispersing hydrogen-type mordenite in an acid solution, the concentration of the acid solution is 0.4-2.5 mol / L, and the amount ratio of hydrogen-type mordenite to acid is 1g:10mL-1g:20mL.
[0013] Furthermore, the temperature of the first calcination and the second calcination is 500-550° C., and the time is 4-6 hours.
[0014] Furthermore, the zirconium sulfate dispersion of acid-treated mordenite is prepared by adding the acid-treated mordenite to a zirconium sulfate solution, the concentration of the zirconium sulfate solution is 0.05-0.2 mol / L, and the amount ratio of the acid-treated mordenite to the zirconium sulfate solution is 1g:10mL-1g:20mL.
[0015] A catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction, wherein the specific surface area of the catalyst ranges from 450 to 550 m 2 / g, the surface area of the catalyst ranges from 80 to 120 m 2 / g, and the mesopore volume of the catalyst is 0.17~0.3cm 3 / g, the micropore volume of the catalyst is 0.15~0.3cm 3 / g.
[0016] Furthermore, the specific surface area of the catalyst ranges from 456 to 525 m 2 / g, the catalyst surface area ranges from 86 to 97 m 2 / g, and the mesopore volume of the catalyst is 0.17~0.2cm 3 / g, the micropore volume of the catalyst is 0.17~0.29cm 3 / g.
[0017] A catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction is used in preparing 2,6-diisopropylnaphthalene.
[0018] Furthermore, the catalyst is filled into a fixed bed reactor, activated under normal pressure and nitrogen gas flow protection, and then naphthalene, isopropanol and cyclohexane are introduced into the fixed bed reactor; at the same time, nitrogen and propylene are introduced into the fixed bed reactor, the reaction pressure is 1-5 MPa, the reaction temperature is 225-325° C., and the reaction is carried out to obtain 2,6-diisopropylnaphthalene.
[0019] Further, the activation temperature is 450-500°C and the time is 1.5-2h;
[0020] The molar ratio of naphthalene, isopropanol and cyclohexane is 1:(0.8-2):(10-30), and the molar ratio of nitrogen and propylene is (2-6):1;
[0021] The mass space velocity of the mixture of naphthalene, isopropanol and cyclohexane is 0.5~5h -1 The mass space velocity of the mixture of nitrogen and propylene is 500~1500h -1 .
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] In the present invention, by treating with an acid dispersion of hydrogen-type mordenite, part of the aluminum atoms in the zeolite framework is effectively removed, while retaining the integrity of its crystal structure. On the basis of the dealuminated zeolite, the present invention further loads heteroatom zirconium through zirconium sulfate treatment. Among them, sulfate ions play a crucial role here: sulfate ions form a sulfated zirconium oxide structure by combining with zirconium oxide in the pores, thereby enhancing the Lewis acidity of the catalyst. At the same time, this sulfated zirconium oxide structure combines with water to generate a stronger Bronsted acid site than the original zeolite. These stronger acid sites allow the reaction to proceed under milder conditions, thereby effectively suppressing tri-substitution and tetra-substitution side reactions that may occur under high temperature conditions. In addition, the introduction of the sulfated zirconium oxide structure reduces the pore size of the zeolite, which is more conducive to the selective catalytic reaction, thereby improving the selectivity of the reaction. In addition, the raw material price of the catalyst is low, the preparation process is simple, and it is easy to achieve industrial application. The raw material price of the catalyst is low, the preparation process is simple, and it is easy to achieve industrial application.
[0024] Furthermore, by treating with an acid solution at a specific concentration (0.4-2 mol / L) and temperature (60-90°C), the present invention effectively removes some aluminum atoms in the zeolite framework while retaining the integrity of its crystal structure. This process introduces mesopores into the zeolite, significantly improving the mass transfer performance of reactants and products on the zeolite surface and in the pores, thereby improving the overall reaction efficiency.
[0025] The catalyst prepared by the present invention is a zeolite catalyst with a multi-level pore structure supported by heteroatoms. Compared with the original mordenite catalyst, the catalyst with a multi-level pore structure supported by heteroatoms has stronger acidity, richer pore structure, and exhibits higher conversion rate, yield and selectivity.
[0026] The present invention adopts isopropanol and propylene as alkylating agents for the isopropylation reaction of naphthalene. Under the action of the catalyst of the present invention, the two reagents undergo an alkylation reaction with naphthalene. Propylene has high reactivity on an acidic catalyst and is very easy to generate carbon cations, which realizes alkylation of the naphthalene ring through electrophilic substitution, thereby ensuring that the alkylation reaction is carried out efficiently. At the same time, isopropanol is dehydroxylated in the reaction to generate byproduct water. On the one hand, the generation of water promotes proton transfer, thereby improving the reaction efficiency; on the other hand, the generated water combines with sulfated zirconium oxide to form a new Bronsted acid site, further promoting the reaction. In addition, water also inhibits the formation of carbon deposits to a certain extent, significantly improving the conversion rate and yield of the reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the XRD spectrum of the catalyst prepared in Example 1;
[0028] Figure 2 is a SEM spectrum of the catalyst prepared in Example 1;
[0029] Figure 3 is a gas chromatogram of a standard mixture of naphthalene, 2-IPN, 1-IPN, 2,6-DIPN and 2,7-DIPN;
[0030] Figure 4 is a gas chromatogram of the initial product of the reaction obtained in Example 1;
[0031] Figure 5 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 1;
[0032] Figure 6 is a gas chromatogram of the initial product of the reaction obtained in Example 2;
[0033] Figure 7 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 2;
[0034] Figure 8 is a gas chromatogram of the initial product of the reaction obtained in Example 3;
[0035] Fig. 9 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 3;
[0036] Fig.10 is a gas chromatogram of the initial product of the reaction obtained in Example 4;
[0037] Fig.11 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 4;
[0038] Fig.12 is a gas chromatogram of the initial product of the reaction obtained in Example 5;
[0039] Fig.13 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 5;
[0040] Fig.14 is a gas chromatogram of the initial product of the reaction obtained in Example 6;
[0041] Fig.15 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 6;
[0042] Fig.16 is a gas chromatogram of the initial product of the reaction obtained in Example 7;
[0043] Fig.17 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 7;
[0044] Fig.18 is a gas chromatogram of the initial product of the reaction obtained in Example 8;
[0045] Fig.19 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 8;
[0046] Fig. 20 is a gas chromatogram of the initial product of the reaction obtained in Example 9;
[0047] Fig.21 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 9;
[0048] Fig. 22 is a gas chromatogram of the initial product of the reaction obtained in Example 10;
[0049] Fig.23 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 10;
[0050] Fig.24 is a gas chromatogram of the initial product of the reaction obtained in Example 11;
[0051] Fig.25 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 11;
[0052] Fig.26 is a gas chromatogram of the initial product of the reaction obtained in Example 12;
[0053] Fig. 27 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 12;
[0054] Fig.28 is a gas chromatogram of the initial product of the reaction obtained in Example 13;
[0055] Fig.29 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 13;
[0056] Fig.30 is a gas chromatogram of the initial product of the reaction obtained in Example 14;
[0057] Fig.31 is a gas chromatogram of the product obtained after 144 hours of reaction in Example 14;
[0058] Fig.32 This is a gas chromatogram of the initial product obtained in Comparative Example 1;
[0059] Fig.33 This is a gas chromatogram of the initial product obtained in Comparative Example 2;
[0060] Fig.34 This is the gas chromatogram of the initial product of the reaction obtained in Comparative Example 3. DETAILED DESCRIPTION
[0061] The present invention will be described more fully below in conjunction with the embodiments. However, the present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0062] The catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction of the present invention is a hydrogen-type mordenite catalyst with a multi-level pore structure loaded with heteroatoms.
[0063] The hydrogen-type mordenite is commercially available sodium-type mordenite.
[0064] A method for preparing a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction of the present invention comprises the following steps:
[0065] Step 1: Disperse 15g of hydrogen-type mordenite in 300mL of 0.4-2mol / L acid solution, treat at 60-90°C for 2-8h under stirring conditions, obtain the treated zeolite by filtration, wash the solid with deionized water until the washing liquid is neutral. Dry for 12-23h in a static air atmosphere at 90-110°C, and then calcine at 500-550°C in static air for 4-6h to obtain acid-treated mordenite.
[0066] Furthermore, the acid solution is an aqueous solution of one or two acids of nitric acid, sulfuric acid, hydrochloric acid or citric acid, and the volume molar concentration of the acid solution is 1 to 1.5 mol / L.
[0067] Step 2: Take 10 g of the acid-treated mordenite obtained in step 1, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.05 to 0.2 mol / L, treat it at 60 to 90° C. for 2 to 8 h under stirring, filter to obtain a solid product, wash the solid product 3 times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 500 to 550° C. in a static air atmosphere for 4 to 6 h to obtain a solid catalyst, tablet, crush, and sieve, and take solid particles of 12 to 20 mesh to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction.
[0068] Preferably, the concentration of the zirconium sulfate solution is 0.08 to 0.15 mol / L.
[0069] The application of the prepared catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction is as follows: the catalyst is filled into a fixed bed reactor, the catalyst is activated for 1.5 to 2 hours under normal pressure conditions under the protection of a 100 mL / min nitrogen gas flow at a temperature of 450 to 500° C., and then the liquid raw materials naphthalene, isopropanol and cyclohexane are stirred at a molar ratio of 1: (0.8 to 2): (10 to 30) for 0.5 to 5 hours. -1 The mass space velocity of 1000 g / min is introduced into the reaction system (fixed bed reactor); at the same time, the gaseous raw materials nitrogen and propylene are introduced into the reaction system (fixed bed reactor) at a mass space velocity of 1000 g / min at a mass space velocity of 1000 g / min at a mass space velocity of 1000 g / min. -1 The volume space velocity is introduced into the reaction system, the reaction pressure is 1-5 MPa, and the reaction temperature is 225-325°C.
[0070] The results show that the reaction conversion rate, yield and selectivity are high, and the catalyst has good anti-carbon deposition performance.
[0071] The technical solution of the present invention is described in detail below through specific embodiments:
[0072] Example 1
[0073] 15g of hydrogen-type mordenite was dispersed in 300mL of 1.5mol / L nitric acid solution, treated at 85°C for 4h under stirring, and the treated zeolite was obtained by filtration. The solid was washed with deionized water until the washing liquid was neutral. The zeolite was dried at 110°C in a static air atmosphere for 12h, and then calcined at 550°C in a static air atmosphere for 4h to obtain acid-treated mordenite.
[0074] Take 10 g of the above-mentioned acid-treated mordenite, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring, filter out a solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0075] See also Figure 1 , it can be seen that the catalyst still maintains the crystal structure of mordenite.
[0076] See also Figure 2 , it can be seen that the particle size of the catalyst is between 50 and 100 nm, and the surface of the catalyst is rough, indicating the existence of even finer nanoparticles.
[0077] The pore characteristics of the catalyst were characterized by nitrogen physical adsorption, and the specific surface area was 487m 2 / g, the catalyst surface area range is 92m 2 / g, and the mesopore volume of the catalyst is 0.19 cm 3 / g, the micropore volume of the catalyst is 0.17cm 3 / g.
[0078] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The tableted solid was crushed and sieved to obtain 12-20 mesh solid particles, which were filled into a fixed bed reactor. The catalyst was activated at 450 °C for 2 h under the protection of a 100 mL / min nitrogen gas flow at normal pressure. Then, the liquid raw materials naphthalene, isopropanol and cyclohexane were stirred at a molar ratio of 1:0.8:20 for 2 h. -1 At the same time, the gaseous raw materials nitrogen and propylene were introduced into the reaction system at a mass space velocity of 4:1 at a rate of 600 h -1 The volume space velocity was introduced into the reaction system, the reaction pressure was 2 MPa, the reaction temperature was 275°C, the reaction time was 144 h, and the reaction product was condensed and collected for gas phase analysis of the product composition.
[0079] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0080] See also Figure 4 and Figure 5 , we can get the following table:
[0081] Table 1 Molecular sieve catalytic reaction results obtained in Example 1
[0082]
[0083]
[0084] See also Figure 3 It can be seen that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0085] See also Figure 4 , it can be seen that…….
[0086] Example 2
[0087] 15g of hydrogen-type mordenite was dispersed in 300mL of 1.5mol / L citric acid solution, treated at 85°C for 4h under stirring, and the treated zeolite was obtained by filtration. The solid was washed with deionized water until the washing liquid was neutral. The zeolite was dried at 110°C in a static air atmosphere for 12h, and then calcined at 550°C in a static air atmosphere for 4h to obtain acid-treated mordenite.
[0088] Take 10 g of the above-mentioned acid-treated mordenite, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring, filter out a solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0089] The pore characteristics of the catalyst were characterized by nitrogen physical adsorption, and the specific surface area was 456 m 2 / g, the catalyst surface area range is 87m 2 / g, and the mesopore volume of the catalyst is 0.20cm 3 / g, the micropore volume of the catalyst is 0.19cm 3 / g.
[0090] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The tableted solid was crushed and sieved to obtain 12-20 mesh solid particles, which were filled into a fixed bed reactor. The catalyst was activated at 450 °C for 2 h under the protection of a 100 mL / min nitrogen gas flow at normal pressure. Then, the liquid raw materials naphthalene, isopropanol and cyclohexane were stirred at a molar ratio of 1:0.8:20 for 2 h. -1 At the same time, the gaseous raw materials nitrogen and propylene were introduced into the reaction system at a mass space velocity of 4:1 at a rate of 600 h -1 The volume space velocity was introduced into the reaction system, the reaction pressure was 2 MPa, the reaction temperature was 275°C, the reaction time was 144 h, and the reaction product was condensed and collected for gas phase analysis of the product composition.
[0091] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0092] See also Figure 6 and Figure 7 , we can get the following table:
[0093] Table 2 Molecular sieve catalytic reaction results obtained in Example 2
[0094]
[0095] Example 3
[0096] Take 20g hydrogen-type mordenite and disperse it in 200mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and wash the solid with deionized water until the washing liquid is neutral. Dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h to obtain acid-treated mordenite.
[0097] Take 10 g of the above-mentioned acid-treated mordenite, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring, filter out a solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0098] The pore characteristics of the catalyst were characterized by nitrogen physical adsorption, and the specific surface area was 525m 2 / g, the catalyst surface area range is 97m 2 / g, and the mesopore volume of the catalyst is 0.18 cm 3 / g, the micropore volume of the catalyst is 0.22cm 3 / g.
[0099] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The tableted solid was crushed and sieved to obtain 12-20 mesh solid particles, which were filled into a fixed bed reactor. The catalyst was activated at 450 °C for 2 h under the protection of a 100 mL / min nitrogen gas flow at normal pressure. Then, the liquid raw materials naphthalene, isopropanol and cyclohexane were stirred at a molar ratio of 1:0.8:20 for 2 h. -1 At the same time, the gaseous raw materials nitrogen and propylene were introduced into the reaction system at a mass space velocity of 4:1 at a rate of 200 h -1 The volume space velocity was introduced into the reaction system, the reaction pressure was 2 MPa, the reaction temperature was 275°C, the reaction time was 144 h, and the reaction product was condensed and collected for gas phase analysis of the product composition.
[0100] See also Figure 3It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0101] See also Figure 8 and Fig. 9 , we can get the following table:
[0102] Table 3 Molecular sieve catalytic reaction results obtained in Example 3
[0103]
[0104] Example 4
[0105] 15g of hydrogen-type mordenite was dispersed in 300mL of 2mol / L nitric acid solution, treated at 85°C for 4h under stirring, and the treated zeolite was obtained by filtration. The solid was washed with deionized water until the washing liquid was neutral. The zeolite was dried at 110°C in a static air atmosphere for 12h, and then calcined at 550°C in a static air atmosphere for 4h to obtain acid-treated mordenite.
[0106] Take 10 g of the above-mentioned acid-treated mordenite, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring, filter out a solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0107] The pore characteristics of the catalyst were characterized by nitrogen physical adsorption, and the specific surface area was 514m 2 / g, the catalyst surface area range is 86m 2 / g, and the mesopore volume of the catalyst is 0.17 cm 3 / g, the micropore volume of the catalyst is 0.29cm 3 / g.
[0108] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The tableted solid was crushed and sieved to obtain 12-20 mesh solid particles, which were filled into a fixed bed reactor. The catalyst was activated at 450 °C for 2 h under the protection of a 100 mL / min nitrogen gas flow at normal pressure. Then, the liquid raw materials naphthalene, isopropanol and cyclohexane were stirred at a molar ratio of 1:0.8:20 for 2 h. -1At the same time, the gaseous raw materials nitrogen and propylene were introduced into the reaction system at a mass space velocity of 4:1 at a rate of 600 h -1 The volume space velocity was introduced into the reaction system, the reaction pressure was 2 MPa, the reaction temperature was 275°C, the reaction time was 144 h, and the reaction product was condensed and collected for gas phase analysis of the product composition.
[0109] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0110] See also Fig.10 and Fig.11 , we can get the following table:
[0111] Table 4 Molecular sieve catalytic reaction results obtained in Example 4
[0112]
[0113] Example 5
[0114] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 60℃ for 4h under stirring, filter and wash the solid with deionized water until the washing liquid is neutral. Dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0115] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring conditions, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0116] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2 h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 275°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0117] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0118] See also Fig.12 and Fig.13 , we can get the following table:
[0119] Table 5 Molecular sieve catalytic reaction results obtained in Example 5
[0120]
[0121] Example 6
[0122] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 6h under stirring, filter and wash the solid with deionized water until the washing liquid is neutral. Dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0123] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring conditions, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0124] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2 h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 275°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0125] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0126] See also Fig.14 and Fig.15 , we can get the following table:
[0127] Table 6 Molecular sieve catalytic reaction results obtained in Example 6
[0128]
[0129]
[0130] Example 7
[0131] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0132] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.2 mol / L, treat it at 85° C. for 4 h under stirring conditions, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0133] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2 h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 275°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0134] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0135] See also Fig.16 and Fig.17 , we can get the following table:
[0136] Table 7 Molecular sieve catalytic reaction results obtained in Example 7
[0137]
[0138] Example 8
[0139] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0140] Take 20 g of the above solid product, disperse it in 200 mL of zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring conditions, filter to obtain a solid product, wash the solid product 3 times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0141] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2 h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 275°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0142] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0143] See also Fig.18 and Fig.19 , we can get the following table:
[0144] Table 8 Molecular sieve catalytic reaction results obtained in Example 8
[0145]
[0146] Example 9
[0147] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0148] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 8 h under stirring, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0149] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2 h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 275°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0150] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0151] See also Fig. 20 and Fig.21 , we can get the following table:
[0152] Table 9 Molecular sieve catalytic reaction results obtained in Example 9
[0153]
[0154] Example 10
[0155] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0156] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 65° C. for 4 h under stirring conditions, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0157] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2 h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 275°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0158] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0159] See also Fig. 22 and Fig.23 , we can get the following table:
[0160] Table 10 Molecular sieve catalytic reaction results obtained in Example 10
[0161]
[0162]
[0163] Embodiment 11
[0164] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0165] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring conditions, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0166] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2 h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 225°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0167] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0168] See also Fig.24 and Fig.25 , we can get the following table:
[0169] Table 11 Molecular sieve catalytic reaction results obtained in Example 11
[0170]
[0171] Example 12
[0172] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0173] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring conditions, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0174] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2 h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 325℃, reaction time was 144h, reaction product was condensed and collected for gas phase analysis of product composition.
[0175] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0176] See also Fig.26 and Fig. 27 , we can get the following table:
[0177] Table 12 Molecular sieve catalytic reaction results obtained in Example 12
[0178]
[0179] Embodiment 13
[0180] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0181] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring conditions, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0182] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:1.2:20; the molar composition of the gas raw material is nitrogen: propylene = 4:1. The mass space velocity of the liquid raw material is 2h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 275°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0183] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0184] See also Fig.28 and Fig.29 , we can get the following table:
[0185] Table 13 Molecular sieve catalytic reaction results obtained in Example 13
[0186]
[0187] Embodiment 14
[0188] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0189] Take 10 g of the above solid product, disperse it in 200 mL of a zirconium sulfate solution with a volume concentration of 0.1 mol / L, treat it at 85° C. for 4 h under stirring conditions, filter out the solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0190] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 450°C for 2 h. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:0.8:20; the molar composition of the gas raw material is nitrogen: propylene = 3:1. The mass space velocity of the liquid raw material is 2h -1 The mass space velocity of the gas phase raw material is 600h -1 , reaction pressure was 2MPa, reaction temperature was 275°C, reaction time was 144h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0191] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0192] See also Fig.30 and Fig.31 , we can get the following table:
[0193] Table 14 Molecular sieve catalytic reaction results obtained in Example 14
[0194]
[0195]
[0196] Embodiment 15
[0197] 15g of hydrogen-type mordenite was dispersed in 300mL of 0.4mol / L nitric acid solution, treated at 60℃ for 8h under stirring, and the treated zeolite was obtained by filtration. The solid was washed with deionized water until the washing liquid was neutral. It was dried at 90℃ in a static air atmosphere for 23h, and then calcined at 500℃ in a static air atmosphere for 6h.
[0198] Take 10 g of the above solid product, disperse it in 150 mL of a zirconium sulfate solution with a volume concentration of 0.08 mol / L, treat it at 60° C. for 8 h under stirring, filter out the solid product, wash the solid product 3 times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 500° C. in static air for 6 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0199] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a 100 mL / min nitrogen gas flow at a temperature of 550°C for 1.5 h, and then the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:2:10; the molar composition of the gas raw material is nitrogen: propylene = 2:1. The mass space velocity of the liquid raw material is 0.5 h -1 The mass space velocity of the gas phase raw material is 500h -1 , reaction pressure is 1MPa, reaction temperature is 225℃, reaction time is 144h, reaction product is condensed and collected for gas phase analysis of product composition. The results are shown in the following table:
[0200] Table 15 Molecular sieve catalytic reaction results obtained in Example 15
[0201]
[0202] Example 16
[0203] 15 g of hydrogen-type mordenite was dispersed in 150 mL of 2 mol / L nitric acid solution, treated at 70°C for 5 h under stirring, and the treated zeolite was obtained by filtration. The solid was washed with deionized water until the washing liquid was neutral. It was dried at 110°C in a static air atmosphere for 13 h, and then calcined at 550°C in a static air atmosphere for 4 h.
[0204] Take 10 g of the above solid product, disperse it in 100 mL of zirconium sulfate solution with a volume concentration of 0.05 mol / L, treat it at 70° C. for 4 h under stirring conditions, filter to obtain a solid product, wash the solid product 3 times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 550° C. in static air for 4 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0205] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated for 2 h in a 100 mL / min nitrogen gas flow at 500 ° C. Then the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1: 1.5: 20; the molar composition of the gas raw material is nitrogen: propylene = 5: 1. The mass space velocity of the liquid raw material is 5h -1 , the mass space velocity of the gas phase raw material is 1000h -1 , reaction pressure is 3MPa, reaction temperature is 325℃, reaction time is 144h, reaction product is condensed and collected for gas phase analysis of product composition. The results are shown in the following table:
[0206] Table 16 Molecular sieve catalytic reaction results obtained in Example 16
[0207]
[0208] Embodiment 17
[0209] 15 g of hydrogen-type mordenite was dispersed in 225 mL of 1 mol / L nitric acid solution, treated at 90°C for 2 h under stirring, and the treated zeolite was obtained by filtration. The solid was washed with deionized water until the washing liquid was neutral. The solid was dried at 100°C in a static air atmosphere for 18 h, and then calcined at 520°C in a static air atmosphere for 5 h.
[0210] Take 10 g of the above solid product, disperse it in 200 mL of zirconium sulfate solution with a volume concentration of 0.15 mol / L, treat it at 90° C. for 2 h under stirring conditions, filter to obtain a solid product, wash the solid product three times with 500 mL of deionized water, dry it at 110° C. in a static air atmosphere for 12 h, and then calcine it at 530° C. in static air for 5 h to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0211] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated in a nitrogen gas flow of 100 mL / min at a temperature of 530°C for 1.5 h, and then the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material is naphthalene: isopropanol: cyclohexane = 1:1.2:30; the molar composition of the gas raw material is nitrogen: propylene = 6:1. The mass space velocity of the liquid raw material is 3h -1 The mass space velocity of the gas phase raw material is 1500h -1 , reaction pressure was 5 MPa, reaction temperature was 290°C, reaction time was 144 h, and reaction products were condensed and collected for gas phase analysis of product composition.
[0212] Table 17 Molecular sieve catalytic reaction results obtained in Example 17
[0213]
[0214] Comparative Example 1
[0215] This comparative example provides a method for preparing a catalyst for a decalinization reaction, comprising the following steps:
[0216] The hydrogen-type mordenite catalyst was tableted on a powder tablet press at a pressure of 10 MPa and a tableting time of 5 min. The obtained solid product was crushed and sieved to obtain 12-20 mesh solid particles. The obtained catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated for 2 h in a 100 mL / min nitrogen gas flow at a temperature of 450 ° C, and then the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material was naphthalene: isopropanol: cyclohexane = 1: 0.8: 20; the molar composition of the gas raw material was nitrogen: propylene = 4: 1. The reaction pressure was 2 MPa, the reaction temperature was 275 ° C, the reaction time was 144 h, and the reaction product was condensed and collected for gas phase analysis of the product composition.
[0217] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0218] See also Fig.32 , we can get the following table:
[0219] Table 18 Comparative Example 1 Molecular Sieve Catalytic Reaction Results
[0220]
[0221] Comparative Example 2
[0222] This comparative example provides a method for preparing a catalyst for a decalinization reaction, comprising the following steps:
[0223] Take 15g hydrogen-type mordenite and disperse it in 300mL of 1.5mol / L nitric acid solution, treat it at 85℃ for 4h under stirring, filter and get the treated zeolite, wash the solid with deionized water until the washing liquid is neutral, dry it at 110℃ in static air atmosphere for 12h, and then calcine it at 550℃ in static air for 4h.
[0224] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated for 2 h in a 100 mL / min nitrogen gas flow at a temperature of 450 ° C. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material was naphthalene: isopropanol: cyclohexane = 1: 0.8: 20; the molar composition of the gas raw material was nitrogen: propylene = 4: 1. The reaction pressure was 2 MPa, the reaction temperature was 275 ° C, and the reaction time was 144 h. The reaction product was condensed and collected for gas phase analysis of the product composition.
[0225] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0226] See also Fig.33 , we can get the following table:
[0227] Table 19 Comparative Example 2 Molecular Sieve Catalytic Reaction Results
[0228]
[0229] Comparative Example 3
[0230] This comparative example provides a method for preparing a catalyst for a decalinization reaction, comprising the following steps:
[0231] Take 10g of hydrogen-type mordenite, disperse it in 200mL of zirconium sulfate solution with a volume concentration of 0.1mol / L, treat it at 85°C for 4h under stirring conditions, filter to obtain a solid product, wash the solid product 3 times with 500mL of deionized water, dry it at 110°C in a static air atmosphere for 12h, and then calcine it at 550°C in static air for 4h to obtain a catalyst for the preparation of 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
[0232] The prepared catalyst was tableted on a powder tablet press at a pressure of 10 MPa for 5 min. The solid product was crushed and sieved to obtain 12-20 mesh solid particles. The catalyst was filled into a fixed bed reactor. Under normal pressure, the catalyst was activated for 2 h in a 100 mL / min nitrogen gas flow at a temperature of 450 ° C. Then, the reaction raw materials were introduced, wherein the liquid raw material was a cyclohexane solution of naphthalene and isopropanol, and the gas raw material was a mixed gas of nitrogen and propylene. The molar composition of the liquid raw material was naphthalene: isopropanol: cyclohexane = 1: 0.8: 20; the molar composition of the gas raw material was nitrogen: propylene = 4: 1. The reaction pressure was 2 MPa, the reaction temperature was 275 ° C, and the reaction time was 144 h. The reaction product was condensed and collected for gas phase analysis of the product composition.
[0233] See also Figure 3 It can be obtained that the retention time of naphthalene is 14.37min, the retention time of 2-IPN is 22.44min, the retention time of 1-IPN is 23.04min, the retention time of 2,6-DIPN is 35.43min, and the retention time of 2,7-DIPN is 36.22min.
[0234] See also Fig.34 , we can get the following table:
[0235] Table 20 Comparative Example 3 molecular sieve catalytic reaction results
[0236]
[0237] According to the above examples 1-14 and comparative examples 1-3, the catalyst prepared by the present invention for preparing 2,6-diisopropylnaphthalene by naphthalene alkylation reaction has a high naphthalene conversion rate and a high 2,6-DIPN selectivity. The initial naphthalene conversion rate is 84.33%-88.58%, and the 2,6-DIPN selectivity is 53.14%-58.84%. After 144 hours of reaction, the naphthalene conversion rate is 78.98%-85.66%, and the 2,6-DIPN selectivity is 49.06%-50.75%. It has good anti-carbon deposition performance, and the molar ratio of 2,6-DIPN to 2,7-DIPN in the product is greater than 2.1, and the molar ratio of 2,6-DIPN to 2,7-DIPN after 144 hours of reaction is greater than 2.2, which is conducive to the subsequent separation of the two.
[0238] The method prepares a heteroatom-loaded hierarchical pore structure zeolite catalyst by acid solution treatment and zirconium sulfate solution treatment. The acid solution treatment can effectively remove part of the aluminum atoms in the zeolite framework, introduce mesopores, and enhance the diffusion performance of reactant and product molecules; the zirconium sulfate treatment forms a sulfated zirconium oxide structure on the zeolite surface, which significantly improves the acidity and selectivity of the catalyst. The obtained catalyst is suitable for the alkylation reaction of naphthalene with isopropanol and propylene in a fixed bed reactor, which significantly improves the conversion rate, yield and selectivity of the reaction, and greatly inhibits the formation of carbon deposits. The preparation process of the present invention is simple, the catalyst cost is low, and it has broad industrial application prospects.
[0239] The heteroatom-loaded hierarchical pore structure zeolite catalyst prepared by the method of the present invention avoids the destruction of the skeleton during the acid treatment process and the loss of active sites, while introducing heteroatom Bronsted acid sites, thereby improving the catalytic activity of the molecular sieve, the selectivity of 2,6-DIPN, the carbon deposition resistance and the molar ratio of 2,6-DIPN to 2,7-DIPN in the product, and still maintains excellent catalytic activity after 144 hours of reaction. These characteristics make the catalyst have great application value in industry.
[0240] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0241] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction, characterized in that: The following steps are involved: The acid dispersion of hydrogen-type mordenite is heat-treated, filtered, and calcined once to obtain acid-treated mordenite; The zirconium sulfate dispersion of acid-treated mordenite is treated at 60-90°C for 2-8 hours, filtered, and calcined twice to obtain a catalyst for preparing 2,6-diisopropylnaphthalene by denaphthalene alkylation reaction.
2. The method for preparing a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction according to claim 1, characterized in that: The heat treatment temperature is 60-90°C and the time is 2-8 hours.
3. The method for preparing a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction according to claim 1, characterized in that: The acid solution is an aqueous solution of one or two acids of nitric acid, sulfuric acid, hydrochloric acid and citric acid.
4. The method for preparing a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction according to claim 1, characterized in that: The acid dispersion of hydrogen-type mordenite is prepared by dispersing hydrogen-type mordenite in an acid solution, the concentration of the acid solution is 0.4-2 mol / L, and the dosage ratio of hydrogen-type mordenite to acid is 1g:10mL-1g:20mL.
5. The method for preparing a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction according to claim 1, characterized in that: The temperature of the first roasting and the second roasting is 500-550°C, and the time is 4-6 hours.
6. The method for preparing a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction according to claim 1, characterized in that: The zirconium sulfate dispersion of acid-treated mordenite is prepared by adding the acid-treated mordenite into a zirconium sulfate solution, the concentration of the zirconium sulfate solution is 0.05-0.2 mol / L, and the dosage ratio of the acid-treated mordenite to the zirconium sulfate solution is 1g:10mL-1g:20mL.
7. A catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction prepared according to the method according to any one of claims 1 to 6, characterized in that: The specific surface area of the catalyst ranges from 450 to 500 m 2 / g, the surface area of the catalyst ranges from 80 to 120 m 2 / g, and the mesopore volume of the catalyst is 0.17~0.3cm 3 / g, the micropore volume of the catalyst is 0.15~0.3cm 3 / g.
8. Use of a catalyst for preparing 2,6-diisopropylnaphthalene by decalinization reaction prepared according to the method of any one of claims 1 to 5 in preparing 2,6-diisopropylnaphthalene.
9. The use according to claim 8, characterized in that: The catalyst is filled into a fixed bed reactor, activated under normal pressure and nitrogen flow protection, and then naphthalene, isopropanol and cyclohexane are introduced into the fixed bed reactor; at the same time, nitrogen and propylene are introduced into the fixed bed reactor, the reaction pressure is 1-5 MPa, the reaction temperature is 225-325° C., and the reaction is carried out to obtain 2,6-diisopropylnaphthalene.
10. The use according to claim 9, characterized in that: The activation temperature is 450-500°C and the activation time is 1.5-2h; The molar ratio of naphthalene, isopropanol and cyclohexane is 1:(0.8-2):(10-30), and the molar ratio of nitrogen and propylene is (2-6):1; The mass space velocity of the mixture of naphthalene, isopropanol and cyclohexane is 0.5~5h -1 The mass space velocity of the mixture of nitrogen and propylene is 500~1500h -1 .